ANALISIS HUBUNGAN KUALITAS KEHIDUPAN KERJA (QUALITY OF WORK LIFE/ QWL) DENGAN SEMANGAT KERJA PEGAWAI DI PUSKESMAS KOTA TANGERANG - , Harmayani; , DR.dr.Sutoto,M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Employee morale in Public Health Center is important being able to provide the best quality service and improve Public Health Center performance. On the other hand, human resource needs and satisfaction are complex and dynamic related with work and performance. One of these needs is necessary and can be assessed through an approach of Quality of Work Life (QWL), which in previous studies has been known that the QWL of service providers can affect the quality of services provided. Objective: 1) Measuring the relationship Quality of Work Life (QWL) with staff morale in public health center. 2) Knowing the dynamics of relationship Quality of Work Life (QWL) with the staff morale in public Health Center. Methode: The research design using a "mixed method", a method for combining quantitative and qualitative approaches. Data collected through questionnaires deployment, documentation and Focus Group Discussion (FGD). Deployment questionnaires conducted on 221 respondents consisting of 52 doctors, 50 midwives, 59 nurses and 60 other health workers. The data collected were analyzed using Spearman Rho statistical analysis techniques to determine the strength of the correlation Quality of Work Life (QWL) with employee morale. Focus Group Discussion is used to further examine how to improve the QWL (to contribute) to the morale. Result and Discussion: From the analysis of the data obtained correlation value of r = 0.611 with p-value = 0.00 <0.05. This shows that there is a significant correlation between QWL with employee morale. The value of correlation is in enough categories. If you see the amount of the value of R2 = 0.373, 37.3% can be explained that morale variance can be explained by changes in the variance of Quality of Work Life (QWL), while the remaining 62.7% is explained by variables beyond the Quality of Work Life (QWL). Largest percentage of respondents rating the doctors, midwives, nurses and other health workers to conditions of Quality of Work Life (QWL) at the health center is in the medium category with enough morale. While less than a quarter provide an assessment of their Quality of Work Life well and showed high morale. Higher morale due to the factor of sincerity, solidarity, awareness and employment initiatives, the opportunity to actualize themselves, and a positive reward. While lack of employee morale due to factor conditions high work participation with multirole employees but has limited competence (non-conformity job needs qualifications with the education/skills of the human resources), labor conflicts are not resolved, the breakdown of communication, and lack of a sense of pride in work and organization. Conclusion and recommendation: There was a significant correlation between QWL with morale employee of public health center in Tangerang City. Quality of Work Life (QWL) will contribute to employee morale through: (1). Creating optimal work participation in accordance with the appropriate competencies. Therefore, the suitability analysis is needed between education / job skills with qualified personnel, and the need for the application of the principle of continuous learning (Continuous Improvement) and through continuous training consistency (Continuing Professional Development). 2) Conflict resolution work with the system and open communication, which can lead to interactions and interpersonal relationships. 3) The need for leaders willing to have two-way communication with employees and facilitate open communication to address the breakdown of communication and coordination, through optimizing staff meeting once a month or at any time when needed. 4) The need for the provision of adequate reward to reinforce positive behaviors and accomplishments that already exist to enhance a sense of pride.